Impact of p53-associated acute myeloid leukemia hallmarks on metabolism and the immune environment - Chomczyk, Monika; Gazzola, Luca; Dash, Shubhankar; Firmanty, Patryk; George, Binsah S.; Mohanty, Vakul; Abbas, Hussein A.; Baran, Natalia (Frontiers in Pharmacology, 2024)
Acute myeloid leukemia (AML), an aggressive malignancy of hematopoietic stem cells, is associated with poor outcomes, especially in elderly patients, due to several genetic and chromosomal aberrations. Tumor protein p53 (TP53) is a key tumor-suppressor gene involved in a variety of cellular processes, including the regulation of apoptosis, metabolism, and the rewiring of the immune environment. Although TP53 mutations are relatively rare in patients with de novo AML, these mutations has been identified as an important molecular subgroup, and patients with these mutations have the worst prognosis and shortest overall survival among patients with AML, even when treated with aggressive chemotherapy and allogeneic stem cell transplant for relapsed or therapy-related AML. Progress in AML genetics and biology has brought the novel therapies, however, the clinical benefit of these agents for patients whose disease is driven by TP53 mutations remains largely unexplored. This review focuses on examining the role of TP53 mutations on such hallmarks of leukemia like metabolic rewiring and immune evasion, the clinical significance of these changes, and the current progress in the therapeutic targeting of mutated p53 and its downstream effects.